Data from: Tetra-EU 1.0: a species-level trophic meta-web of European tetrapods - Maiorano, Luigi; Montemaggiori, Alessandro; Ficetola, Gentile Francesco; O'Connor, Louise; Thuiller, Wilfried (Zenodo, 2021)
Motivation Documenting potential interactions between species represents a major step to understand and predict the spatial and temporal structure of multi-trophic communities and their functioning. The metaweb concept summarises the potential trophic (and non-trophic) interactions in a given species-pool. As such, it generalises the regional species-pool of community ecology by incorporating the potential relationships between species from different trophic levels along with their functional characteristics. However, while this concept is theoretically very attractive, it has rarely been used to understand the structure of ecological network, mostly because of data availability. Here, we provide a continental scale, species-level, metaweb for all tetrapods (mammals, breeding birds, reptiles, amphibians) occurring in Europe and in the Northern Mediterranean basin. This metaweb is based on data extracted from scientific literature, including published papers, books, and grey literature. Main type of variable contained For each species considered, we built the network of potential 2-way trophic interactions. Spatial location and grain We considered all species occurring in the entire European sub-continent, from Macaronesia (including only the islands politically belonging to Spain and Portugal) to the Ural Mountains (west to east), and from Fennoscandia and UK islands to the Mediterranean (north to south). We included Turkey, geographically part of Asia, to provide a complete picture of the north-eastern Mediterranean coast. Time period The data represent information published and/or collected during the last 50 years. Major taxa studied and level of measurement We focused our metaweb on terrestrial tetrapods occurring in the study area. Only species introduced in historical times and currently naturalized were considered; novel introductions were excluded. In total we included 288 mammals, 509 regularly breeding birds, 250 reptiles, and 104 amphibians. Software format Data are supplied as semi-colon separated ...